Dakwah Islam Di Era Milenial - Abdul Ghofur (Dakwatuna: Jurnal Dakwah dan Komunikasi Islam, 2019)
This article seeks to explain the dynamics of Islamic da'wah experienced by da'i in the face of increasingly modern times. This paper has a focus on how to preach in the millennial era by preparing preachers to be able to adapt to the development of science and technology so that they can utilize various communication and information media that are widely used by millennials. Key words: Islamic da'wah, millennial, adaptation.